2000
DOI: 10.1159/000029513
|View full text |Cite
|
Sign up to set email alerts
|

Soot-Exposed Mononuclear Cells Increase Inflammatory Cytokine mRNA Expression and Protein Secretion in Cocultured Bronchial Epithelial Cells

Abstract: Background: Soot particles are air pollutants capable of inducing airway and lung parenchymal injury. Mononuclear and bronchial epithelial cells are central to the maintenance of homeostasis and inflammation in the airways. Objectives: The aim of this study was to evaluate the contribution of mononuclear cells to the release of inflammatory mediators by bronchial epithelial cells. Methods: To model the in vivo situation, an in vitro system of cocultured blood monocytes and BEAS-2B cells was established in a tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2005
2005
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…A further cytokine that has been studied in a sufficient number of experiments to allow for a comparative analysis, is TNF-α. The results are also included in Table 5 for different concentrations of (Becker et al, 2005a(Becker et al, , 2005bCarter et al, 1997;Drumm et al, 2000;Dybing et al, 2004;Fujii et al, 2001Fujii et al, , 2002Garcon et al, 2006;Gilmour et al, 2003Gilmour et al, , 2005Hetland et al, 2004;Inoue et al, 2007;Ishii et al, 2004Ishii et al, , 2005Jimenez et al, 2002;Li et al, 2002;Mazzarella et al, 2007;Osornio-Vargas et al, 2003;Payne et al, 2004;Reibman et al, 2002Reibman et al, , 2003Stringer & Kobzik, 1998;Tao & Kobzik, 2002;Wottrich et al, 2004;Wu et al, 2001) particles and exposure times. Significant effects were observed at a concentration of about 50 µg/mL over time periods ranging between 9 and 24 hours.…”
Section: Cell Types Particle Types and Outcome Measures Usedmentioning
confidence: 99%
See 2 more Smart Citations
“…A further cytokine that has been studied in a sufficient number of experiments to allow for a comparative analysis, is TNF-α. The results are also included in Table 5 for different concentrations of (Becker et al, 2005a(Becker et al, , 2005bCarter et al, 1997;Drumm et al, 2000;Dybing et al, 2004;Fujii et al, 2001Fujii et al, , 2002Garcon et al, 2006;Gilmour et al, 2003Gilmour et al, , 2005Hetland et al, 2004;Inoue et al, 2007;Ishii et al, 2004Ishii et al, , 2005Jimenez et al, 2002;Li et al, 2002;Mazzarella et al, 2007;Osornio-Vargas et al, 2003;Payne et al, 2004;Reibman et al, 2002Reibman et al, , 2003Stringer & Kobzik, 1998;Tao & Kobzik, 2002;Wottrich et al, 2004;Wu et al, 2001) particles and exposure times. Significant effects were observed at a concentration of about 50 µg/mL over time periods ranging between 9 and 24 hours.…”
Section: Cell Types Particle Types and Outcome Measures Usedmentioning
confidence: 99%
“…As in table 4, the total numbers do not necessarily equal the number of experiments or studies, since authors might have investigated more than one cytokine in a study. Eight studies evaluated IL-6 (Carter et al, 1997;Drumm et al, 2000;Fujii et al, 2002;Ishii et al, 2004Ishii et al, , 2005Mazzarella et al, 2007;Payne et al, 2004;Wottrich et al, 2004), and twelve studies evaluated IL-8 (Carter et al, 1997;Drumm et al, 2000;Garcon et al, 2006;Gilmour et al, 2003;Hetland et al, 2004;Ishii et al, 2004;Li et al, 2002;Mazzarella et al, 2007;Payne et al, 2004;Schins et al, 2000;Stringer and Kobzik, 1998;Wottrich et al, 2004). Finally, TNF-α data are based on 6 references Fujii et al, 2002;Garcon et al, 2006;…”
Section: Monocytes/macrophages Cytokine Release and Mrna Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are, of course, other cells present in intact lungs that may independently provide an additional response or alter the response seen by alveolar macrophages. It is known, for example, that macrophage-epithelium interactions enhance the innate immune cytokine response to hyperoxia, particulants, and other toxins (8,16,17,25,28). We deliberately limited our studies to the interaction of spores with macrophages and diminished possible effects of germinated bacteria by using gentamicin in the medium.…”
mentioning
confidence: 99%
“…IP-10 was found in both epithelial cells and macrophages, suggesting that both types of cell participate and cooperate in the innate immune response that is responsible for the influx of inflammatory cells seen in Ad7 infection, and both cell types produce IP-10 in other systems (Pechkovsky et al, 2005;Tibbles et al, 2002;Zaiss et al, 2009). It has been shown that interactions between macrophages and epithelial cells promote inflammatory responses to hyperoxia, particulates and other toxins (Drumm et al, 2000;Hjort et al, 2003;Lee & Rannels, 1996;Sharma et al, 2004;Tao & Kobzik, 2002). Elegant work by D'Angio and co-workers demonstrated that cell-cell contact of THP-1 monocyte/macrophages and A549 epithelial cells is important for extracellular and intracellular IL-8 induction by hyperoxia in co-cultured THP-1 cells (Hjort et al, 2003).…”
Section: Discussionmentioning
confidence: 99%